Assessment of Nutritional Status Among Adult Girls at Peshawar - Attaullah, Shahnaz; Ghulfam, Naila; Tayyab, Seemab; Rahim, Sheema; Wadood, Umair; Wadood, Noreen (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES The aim of this study was to examine the relation of Mid Upper Arm Circumference (MUAC) with Body Mass Index (BMI) and waist-to-hip ratio among adult girls. METHODOLOGY A descriptive or cross-sectional study was conducted among adolescent girls 18 plus by BS students at Jinnah college for the women’s University of Peshawar, in collaboration with Pakistan Health Research Council (PHRC) Khyber Medical College Peshawar. MUAC is a useful cheap, and non-invasive technique used for the assessment of nutritional status that has important effects on health in recovery from illness. The analysis of data was conducted as a review of the filled questionnaire. The statistical relationship between variables and their prevalence was assessed using the Chi-Square test. RESULTS Results showed that according to MUAC 20.8% and BMI of 22.55% adult girls were underweight. Our study also revealed that 7(5.83%) adult females were underweight according to MUAC measurements but had normal BMI with a statically significant value of p 0.000. In correlation with waist-hip ratio and MUAC, 24.2% of adult females were having an unacceptable hip ratio (which means that their waist-to-hip ratio is either average, high, or extreme) but had normal MUAC. This correlation between MUAC and waist-to-hip ratio was also highly significant (p 0.046). Besides, we also got the measurements of obese and overweight girls. CONCLUSION In this study, mid-upper arm circumference (MUAC) was statistically and significantly correlated with body mass index (BMI) (p=0.000). As MUAC is a very simple and inexpensive method to assess nutrition, so this is a very good tool to be used in underdeveloped countries like Pakistan.